Structural Model for Fibre-Reinforced Precast Concrete Sandwich Panels - Luis Segura-Castillo; Nicolás García; Iliana Rodríguez Viacava; Gemma Rodríguez de Sensale (Advances in Civil Engineering)
Fibre-reinforced concrete (FRC) has been used in numerous types of precast elements around the world, as has been shown that reductions in production costs and time can be obtained; however, there is little experience of this material in Uruguay. Therefore, our study analysed the feasibility of its utilisation in this country. This paper reports on the development of a simple analysis model that is useful for the design of FRC precast elements. The model efficiency was evaluated through its application to a practical case study—vertical precast concrete sandwich panel systems tested by bending. Three different types of reinforcement were analysed: synthetic fibres, metal fibres, and steel mesh. With the developed model, the cost-efficiency of different panel geometries and amounts of reinforcement were evaluated. The model allowed consideration of the contribution of the fibres to withstand internal tensile forces of the panels and therefore be able to substitute for the steel mesh in the panel wythes. It was found that it was possible to optimise panel reinforcement and geometry, thereby reducing wythe thickness. Besides the reduction in production time, it was possible to achieve cost savings of up to 10% by replacing steel mesh with fibres and of more than 20% if the geometry was also modified.